Studi Perencanaan Campuran Beton dengan Penambahan Superplasticizer dan Penggunaan Silica Fume Sebagai Pengganti Sebagian Semen - Israel Padang (Journal Dynamic Saint, 2020)
One of the problems that greatly affects the compressive strength of concrete is the presence of porosity, which is also influenced by the size and size of the cement water factor used. To reduce this problem, additives can be used to improve the strength performance of concrete, especially for high strength concrete, namely silica fume and superplasticizer.The purpose of this study was to determine the effect of adding superplasticizer and silica fume as a partial substitute for cement on the compressive strength of high strength concrete. In this study an experimental method was used by testing a sample with a superplasticizer composition of 1% for all variations and the use of silica fume as a partial replacement for cement at 5%, 10%, and 15% of the weight of cement using a cylinder specimen of 15 cm diameter and 30 cm, f'c plan 40 MPa tested at the age of 28 days with treatment before testing In this study, the normal compressive strength of concrete at 28 days was 39.632 Mpa, for the addition of 1% superplasticizer and 5% silica fume f'c = 43.878 Mpa, and for the addition of 1% superplasticizer and 10% silica fume f'c = 44.161 Mpa. Then for the addition of 1% superplasticizer and 15% silica fume f'c = 46,992 Mpa. Based on these results, it shows that the addition of 1% superplasticizer and 15% silica fume as a substitute for some cement can increase the compressive strength of high quality concrete.